The effect of special force Training for running the relay in the development and achievement of velocity ran 4 × 100 m junio mail - Majeed, Sanaa; Abedulreda, Sadiq (Journal of Physical Education, 2015)
Ran (4 x 100) Relay depends on the individual abilities of players who make up the collective work and the choice of the type and capacity of the player to suit the player’s abilities and that the time for cutting these distances depends on its ability to accelerate high definition player and maintain them from top speed the contestants and conduct objective research to identify time (30 m) for the receipt and delivery of distance stability, movement and force a sample search and preparation of special exercises, as well as to identify the impact ofThese exercises on the velocity and the researcher used experimental method and included a sample of research (8) of runners ran registered and conducted test achievement ran the 4 x 100 m relay by using video and photography test ran (30 m) from a standing position and. the researcher tests tribal dated 14/2/2015 and the researcher application (24) during the training unit (3) training units per week and the researcher tests remote 14/4/2015 and research findings were the ability to accelerate may develop improved resilience appeared speed and back harmony between the spatial and temporal domain for transition